Mandarin Chinese visual dictionary - Lin, Luan; Reid, Lauren (Collins, 2019)
Immerse yourself in this photographic guide to the key words and phrases in Chinese. This attractive book is perfect for travelling and provides a practical guide to Chinese language and culture. Everyday words are arranged in themes with carefully selected up-to-date images to illustrate key words and phrases, and a two-way index enabling you to find words quickly as you learn. All essential words and phrases for modern life in China are at your fingertips with topics covering home life, work and school environments, shopping, food and drink, sport and leisure, transport, technology, and the environment. Great care has been given to represent modern Chinese culture and enhance your experience of China and its people, including food and drink, customs, celebrations, and festivals.